2000
DOI: 10.1002/1521-3757(20000616)112:12<2236::aid-ange2236>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Efficient Triplet Analogue of a Thermal Biradical Cyclization—The Photochemical C2–C6 Cyclization of Enyne-Heteroallenes

Abstract: In einer mit hohen Ausbeuten verlaufenden Photoreaktion (90–99%) cyclisieren Enin‐Carbodiimide (X=N; siehe Schema) innerhalb von wenigen Minuten zu Indolochinolinen. Analog können Enin‐Ketenimine (X=CAr) zu Benzocarbazolen photocyclisiert werden, wodurch der Zugang zu photoaktiven Prodrugs eröffnet wird.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This photolytic reaction proceeds via the triplet analogues to the thermal diradical cyclization. The photolysis of the enyne ketenimines 729 in degassed toluene in a Rayonet RPR-100 photochemical reactor at 254 nm afforded the 5 H -benzo[ b ]carbazoles 730 (Scheme ) . The low yield of the 5 H -benzo[ b ]carbazoles 730 was ascribed to the formation of polymeric material.…”
Section: 17 Cycloaromatization Of N-[2-(1-alkynyl)phenyl]keteniminesmentioning
confidence: 99%
“…This photolytic reaction proceeds via the triplet analogues to the thermal diradical cyclization. The photolysis of the enyne ketenimines 729 in degassed toluene in a Rayonet RPR-100 photochemical reactor at 254 nm afforded the 5 H -benzo[ b ]carbazoles 730 (Scheme ) . The low yield of the 5 H -benzo[ b ]carbazoles 730 was ascribed to the formation of polymeric material.…”
Section: 17 Cycloaromatization Of N-[2-(1-alkynyl)phenyl]keteniminesmentioning
confidence: 99%
“…In contrast, when 4 was irradiated without triplet sensitization (toluene, λ = 300 nm) no reaction was observed after 90 minutes. Previous mechanistic results [7] exclude a singlet reaction and suggest a pathway via the triplet excited state of the carbodiimide unit [12] which then triggers ring closure to the biradical 6, formally by an 5-exodig cyclization. 6 can be understood as a triplet analogue of the biradical that is formed in the thermal C 2 -C 6 cyclization of enyne-(hetero)allenes [4,6].…”
Section: Methodsmentioning
confidence: 93%
“…C 2 -C 6 cyclization). Recently, it was demonstrated that the thermal C 2 -C 6 cyclization of enyne-carbodiimides and enyneketenimines [6] can be complemented by a very efficient triplet sensitized photochemical route [7]. As the latter reaction has important consequences with regards to the development of photoactive prodrugs, e.g.…”
Section: Introductionmentioning
confidence: 99%